Reasonable woman [compact disc] - Sia (Singer) (Atlantic ; Monkey Puzzle Records, 2024)
Sia's first proper album since 2016 is so filled to the brim with pop perfection, it almost overwhelms with how effortless it is for her to craft such instantly connectable songs. The collection is everything Sia does best, and the sonic equivalent of a myriad of things: an empowering embrace, secrets told late at night, going to the best party in the world, the vulnerability of declaring you love someone, the steadfast determination to keep going, even if your love isn't returned; the messiness of being human; the exuberance of being human. In essence, it is life happening to us, happening for us; the songs mirror back to us being alive with every chorus.